The theoretical and experimental determination of certain design parameters for the stressed skin design method for single storey steel frame buildings - Hattingh, Louis Cristiaan (Stellenbosch : Stellenbosch University, 2012)
Project (M. Ing.) -- University of Stellenbosch, 1993.